1998
DOI: 10.1046/j.1469-8137.1998.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition and ectomycorrhizas

Abstract: As a result of increasing anthropogenic nitrogen deposition, N availability in many forest ecosystems, which are normally N-limited, has been enhanced. We discuss the impacts of this increased N availability on the ectomycorrhizal (ECM) symbiosis which is generally regarded as an adaptation to nutrient limited conditions. Nitrogen deposition can influence fruit-body formation by ECM fungi, the production and distribution of the extraradical mycelium in the soil and the formation of ectomycorrhizas.Avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
190
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(206 citation statements)
references
References 134 publications
(121 reference statements)
15
190
0
1
Order By: Relevance
“…Soil base saturation, pH and organic matter content are among the most important factors governing the distribution of macrofungi (Agerer et al 1998;Erland and Taylor 2002;Wallenda and Kottke 1998;Kernaghan 2005). Whereas organic matter content did not differ between the two treatments, the soil pH and base saturation were significantly reduced in the N plot in the course of our experiment (Table 1).…”
Section: Response Of Saprobic Species To Fertilizationmentioning
confidence: 71%
See 2 more Smart Citations
“…Soil base saturation, pH and organic matter content are among the most important factors governing the distribution of macrofungi (Agerer et al 1998;Erland and Taylor 2002;Wallenda and Kottke 1998;Kernaghan 2005). Whereas organic matter content did not differ between the two treatments, the soil pH and base saturation were significantly reduced in the N plot in the course of our experiment (Table 1).…”
Section: Response Of Saprobic Species To Fertilizationmentioning
confidence: 71%
“…The critical loads for N in Swiss forests are within the range of 8-20 kg N ha -1 year -1 (Waldner et al 2007). Bobbink et al (1992) cited in Wallenda and Kottke (1998) suggested critical loads of 15-20 kg N ha -1 year -1 for changes in sporocarp production of ectomycorrhizal fungi. This means that the atmospheric N input in our site at least reaches or probably exceeds critical loads affecting forest ecosystems in general and ectomycorrhizal sporocarps in particular.…”
Section: Changes Of Fungal Communities Over Time Irrespective Of N Trmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that high inorganic N additions can lead to changes in EMF community structure (Wallenda & Kottke, 1998;Lilleskov et al , 2001Lilleskov et al , , 2002Peter et al , 2001). We characterized the dominant EMF taxa over an N deposition gradient in Alaska and found that with increasing N availability most taxa declined both in sporocarp production and in abundance on root tips, and that the dominant taxa changed (Lilleskov et al , 2001(Lilleskov et al , , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Some ectomycorrhizal symbiotic fungi inhibit pathogens (Rudawska 1990), probably due to metabolites produced by symbiotic fungi and synthesized in roots (Oleksyn 1998). Symbionts seem to be sensitive to the high amount of N applied (Wallenda and Kottke 1998). Some other research point out the negative influence of fertilization, negative effect of high fertilization is the decrease tree resistance to insects (Glynn and Herms 2001).…”
Section: Fertilization Alters Tree Physiological Conditionmentioning
confidence: 99%